use the residue of Pinus spp, high reactivity metakaolin and residue of ceramic calcined in wood-cement composites - Miranda de Lima, Adauto José; Iwakiri, Setsuo; Lomelí-Ramírez, María Guadalupe (Instituto de Ecología, A.C., 2016)
This research was developed with the objective of evaluating the potential use of residues of the production of sown Pinus spp wood and partial substitutions of Portland cement for high performance metakaolin and residue of calcined ceramic in cement-wood composites. The evaluation of the physical characteristics (specific mass, porosity and water absorption) and mechanics characteristics (compression and traction resistances) of the composites were determined in agreement with the ABNT standards. The was levels of substitution to the Portland cement for 5% to 40% of high performance metakaolin and 5% to 40% of residue of calcined ceramic. In both cases additive chemicals (CaCl2.2H2O) to speed up the cure of the cement were used and super-plasticizer to maintain without altering the rheological characteristics of the composite. The results demonstrated the technical viability to the use of the residue of Pinus spp and the for substitutions of the cement Portland in composites, and the optimized levels, obtained through multivariate statistical analysis, were 10% of high performance metakaolin and  5% of residue of calcined ceramic.